Implementation of federal laws in the regions - إسماعيل نجم الدين زنكنة; دانا عبدالكريم سعيد (QALAAI ZANIST JOURNAL, 2019)
In the Iraqi model of federalism, the federal legislature is enacting legislation that is tend to be implemented in its constituent regions. However, there is only one region within Iraq, the Kurdistan Region. Despite the fact that establishing other region in Iraq is not contradicting with legal and constitutional statutes, no other regions have been established in Iraq. What should be looked into in the mechanism of legislations issued by the Iraqi Parliament within Kurdistan Region is that: is it necessary to implement all the laws in the Kurdistan Region? Taken into consideration that the Iraqi Parliament is enacting two types of legislations, local and federal legislations. This led us to make differentiation between the two types of legislation and thus the mechanism of implementation of such legislation within the Kurdistan Region and those provinces outside Kurdistan Region. The constitutional areas that the federal legislature is entitled to issue are four, including: exclusive competencies, common competencies, competences related to the establishment of federal bodies and their institutions, and the sparse aspects. As for the implementation of the federal laws in the provinces or the Kurdistan Region of Iraq, the result is the adoption and application of the mixed management or implementation method, given that the federal government itself implements federal laws, especially those relating to the majority of exclusive competencies that it practiced by the federal authorities. Besides, there are federal laws implemented through a joint administration between the federal government and the Regional Government (such as the Customs Law, the Antiquities Law, Oil and Gas Law ...etc. The study concluded that two proposals were submitted to the constitutional legislator and the ordinary law legislator in Iraq in order to determine the nature of the federal legislation and separate it from the domestic legislation, and thus to explicitly stand on the mechanism of implementation of federal laws in the regions.